MODEL PEMAKNAAN NASIONALISME MASYARAKAT PULAU SEBATIK KALIMANTAN TIMUR - Muhammad Hairul Saleh (Jurnal Borneo Administrator, 2011)
This study is aimed to know the understanding models of Sebatik Island's people about nationalism. Using phenomenological approach, the result of this study indicates that there are three models of society understanding about nationalism. They are the understanding by society who have Identity Card of Indonesia (established people), understanding by society who have Identity Card both  Indonesia and Malaysia or double citizenship, and nationalism understanding of society being Malaysia citizen (Malaysian loves Indonesia). The first and the second models are elaborated based on some indicators, such as ownership of identity card, currency, economics, language, education, political participation, celebration of Republic of Indonesia's independence day, and Ambalat case; and the third model is a description to complete the first and the second models explanation. Keywords : understanding, nationalism, society of Sebatik Island, Indonesia-Malaysia border.Penelitian ini bertujuan untuk mengetahui model pemaknaan masyarakat Pulau Sebatik terhadap nasionalisme. Dengan menggunakan pendekatan fenomenologik, hasil penelitian menunjukkan terdapat tiga model pemaknaan masyarakat terhadap nasionalisme, yakni pemaknaan oleh masyarakat yang hanya memiliki KTP Indonesia (orang tempatan), pemaknaan oleh masyarakat yang memiliki KTP Indonesia dan ID Card Malaysia atau berkewarganegaraan ganda, dan pemaknaan nasionalisme masyarakat yang telah menjadi warga negara Malaysia (orang Malaysia yang cinta Indonesia). Model pertama dan kedua dielaborasi berdasarkan beberapa indikator, seperti kepemilikan KTP, mata uang, ekonomi, bahasa, pendidikan, partisipasi politik, perayaan HUT kemerdekaan RI, dan kasus Ambalat, sedangkan model ketiga hanya berupa penggambaran untuk melengkapi menjelasan model pertama dan kedua. Kata kunci : pemaknaan, nasionalisme, masyarakat Pulau Sebatik, perbatasan Indonesia-Malaysia